The economics of TARGET2 balances - Ulrich Bindseil; Philipp Johann König (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
It has recently been argued that intra-eurosystem claims and liabilities in the form of TARGET2 balances would raise fundamental issues within the European monetary union. This article provides a framework for the economic analysis of TARGET2 balances and discusses the key arguments behind this recent debate. The analysis is conducted within a system of financial accounts in which TARGET2 balances can arise either due to current account transactions or cross-border capital ows. It is argued that the recent volatility of TARGET2 balances reflects capital flow movements, while the previously prevailing current account positions did not find a strong reflection in TARGET2 balances. Some recent statements regarding TARGET2 appear to be due to a failure to distinguish between the monetary base (a central bank liability concept) and the liquidity deficit of the banking system vis-à-vis the central bank (a central bank asset concept). Furthermore, the article highlights the importance of TARGET2 for the stability of the euro area and points out that the proposal to limit the size of TARGET2 liabilities essentially contradicts the idea of a monetary union.
Keywords: E58; F33; F55; 330; TARGET2; central bank balance sheet; liquidity deficit; financial crisis; Internationaler Zahlungsverkehr; Verrechnungsverkehr; Auslandsverschuldung; Zahlungsbilanzungleichgewicht; Bankenliquidität; Geldbasis; Europäische Wirtschafts- und Währungsunion; Eurozone